Program Pendidikan Keaksaraan Keluarga dalam Rangka Menumbuhkan Minat Baca Masyarakat Desa Kasemen Kec. Kasemen Serang Banten - Herlina Siregar; Dadan Darmawan (Universitas Mathla'ul Anwar Banten, 2022)
FAMILY LITERACY EDUCATION PROGRAM IN THE CONTEXT FOSTERING READING INTEREST IN THE KASEMEN VILLAGE COMMUNITY, KASEMEN SERANG BANTEN. One of the alternative programs to eradicate illiteracy is literacy education which is considered strategic and is the basis of knowledge for all human beings (the essential learning needs). the low interest in reading in the community, especially school-age children due to the lack of support and involvement of parents in facilitating children's reading needs, is a major problem so that it is agreed between the proposer and partners to be solved together through mentoring each family in literacy learning, where later partners will gain knowledge (understanding) and experiences that can be implemented in everyday life in the family so that the growth of reading habits will have an impact on increasing reading culture in society. The specific purpose of PKM activities is to foster children's interest in reading by involving parents through family literacy education. The methods used to achieve the objectives of PKM activities are mapping of activity participants, implementation of family education program training, implementation of literacy programs in families, evaluation. This activity was carried out at TBM Ummatan Wasathon and PAUD SMART with a period of 8 months from April – November 2021. Based on a survey on service activities, it can be concluded that the habit of reading by parents in Kasemen village is considered very important to be implemented from an early age. There is support from the institution and the enthusiasm of the participants so that the activities can be carried out properly without significant obstacles. Training participants receive benefits after receiving training in reading strategies and methods for children in the form of increased understanding and experience in implementing reading habits in the family which is expected to create a reading culture in the community.